A Comparative View on Sex Differentiation and Gametogenesis Genes in Lungfish and Coelacanths. (29th May 2018) - Biscotti, Maria Assunta; Adolfi, Mateus Contar; Barucca, Marco; Forconi, Mariko; Pallavicini, Alberto; Gerdol, Marco; Canapa, Adriana; Schartl, Manfred
Abstract: Gonadal sex differentiation and reproduction are the keys to the perpetuation of favorable gene combinations and positively selected traits. In vertebrates, several gonad development features that differentiate tetrapods and fishes are likely to be, at least in part, related to the water-to-land transition. The collection of information from basal sarcopterygians, coelacanths, and lungfishes, is crucial to improve our understanding of the molecular evolution of pathways involved in reproductive functions, since these organisms are generally regarded as "living fossils" and as the direct ancestors of tetrapods. Here, we report for the first time the characterization of >50 genes related to sex differentiation and gametogenesis in Latimeria menadoensis and Protopterus annectens . Although the expression profiles of most genes is consistent with the intermediate position of basal sarcopterygians between actinopterygian fish and tetrapods, their phylogenetic placement and presence/absence patterns often reveal a closer affinity to the tetrapod orthologs. On the other hand, particular genes, for example, the male gonad factor gsdf ( Gonadal Soma-Derived Factor ), provide examples of ancestral traits shared with actinopterygians, which disappeared in the tetrapod lineage.